This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Without loss of generality, a , b > 0 . We can write a sin x + b cos x = R sin ( x + ϵ ) a cos x − b sin x = R cos ( x + ϵ ) where R = a 2 + b 2 and 0 < ϵ < 2 1 π and tan ϵ = a b . Thus we want to maximize ∣ R sin ( x + ϵ ) − 1 ∣ + ∣ R cos ( x + ϵ ) ∣ x ∈ R which is the same as maximizing f ( x ) = ∣ R sin x − 1 ∣ + R ∣ cos x ∣ x ∈ R We note that 0 ≤ f ( x ) ≤ R ( ∣ sin x ∣ + ∣ cos x ∣ ) + 1 ≤ R 2 + 1 x ∈ R and we note that f ( − 4 1 π ) = R 2 + 1 and so the maximum value of f ( x ) is R 2 + 1 . Since this is equal to 1 1 , we deduce that R = 5 2 , so a 2 + b 2 = 5 0 .